Criminal Accountability of Perpetrators of Child Molestation Supreme Court Decision Number 1041/K/Pid.Sus/2020 - Muhammad Arif Prasetyo; Rodiatun Adawiyah; Widodo Ramadhana; Hebri Gokman Lumbantungkup (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2024)
The crime of molestation is a form of crime against decency, where criminal acts and criminality can be committed by anyone, whether parents, adults, teenagers and children, either directly or indirectly. However, children are very vulnerable to physical or sexual violence because they are powerless creatures who depend on the people who are present in their lives to be able to keep them alive in the world safely. The purpose of this study is to find out how the criminal liability of perpetrators of child molestation and to find out how the legal considerations of judges in handling criminal cases in accordance with the Supreme Court Decision Number 1041 / K / Pid.Sus/2020. The author uses the Normative Legal research method with a Normative Juridical approach. The source of legal material used consists of primary legal material, secondary legal material, and tertiary legal material. In this study, the authors used data collection techniques in the form of literature studies (library search). Data analysis techniques use qualitative data analysis to find out and explore certain phenomena. In this study, the authors examined the Crime of Child Molestation under the age of the defendant Syarifuddin bin Alm, Tayat at the Level of Justice of the Seluma District Prosecutor's Office sentenced the perpetrator to imprisonment, fines and was proven guilty and convincing of the accused crime of molestation based on witness testimony, instructions, evidence, and defendant's statement.